Innovation of streetlight at curved roads / Nurin Husnina Hussin and Azira Ibrahim - Hussin, Nurin Husnina; Ibrahim, Azira (2023)
Streetlight has been used for the first time in London to brighten up the town during winter. As time goes by, the development of streetlight usage has been advanced globally and that includes Malaysia. However, the current road condition in Malaysia requires an improvement since road has become one of the important elements in people’s daily lives. There are several areas on roads that require curved roadwork to preserve nature. The percentage of accidents on curved roads is higher compared to straight roads, since drivers’ visibility is limited, especially at night when they may not notice oncoming cars from another lane. Hence, the current streetlight has several limitations that contribute to increased carbon emissions in our atmosphere. Since roadworks are the primary means of access for everyone and are used in people’s daily lives, ensuring the safety of road users while also protecting the environment need to be a priority. This can be achieved by innovating streetlights on curved roads with the incorporation of solar panels and PIR sensors.